2016
DOI: 10.21548/33-2-1115
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Effect of Micro-oxygenation before Malolactic Fermentation on South African Pinotage Red Wine with Different Colour and Phenolic Analyses

Abstract: The use of micro-oxygenation and its effect on the quality of the red wine varietal, Pinotage, is largely unknown. The influence of adding different oxygen dosages before malolactic fermentation on the phenolic composition and colour stabilisation of wine made from Pinotage was studied, and the suitability of certain spectrophotometric and RP-HPLC analyses to determine these changes were assessed in tanks of commercial lengths. Total oxygen dosages of 0 mg/L, 16 mg/L and 32 mg/L were applied, after which the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
1
5
2
Order By: Relevance
“…When the samples were coloured according to the C/Ox treatment, the samples were distributed along the PC2 axis (21.3%), with Ox samples being characterised by a generally higher phenolic and especially tannin concentrations (Figures 2 and 3). Contrary to the findings of Geldenhuys et al (2012), oxygen was also found to play an important role in tannin concentrations (Figure 2 A3). However, Geldenhuys et al (2012) applied progressive micro-oxygenation, whereas in this study a large amount of oxygen was added at a time.…”
Section: Colour and Phenolic Evolution Of The Final Extractscontrasting
confidence: 90%
See 1 more Smart Citation
“…When the samples were coloured according to the C/Ox treatment, the samples were distributed along the PC2 axis (21.3%), with Ox samples being characterised by a generally higher phenolic and especially tannin concentrations (Figures 2 and 3). Contrary to the findings of Geldenhuys et al (2012), oxygen was also found to play an important role in tannin concentrations (Figure 2 A3). However, Geldenhuys et al (2012) applied progressive micro-oxygenation, whereas in this study a large amount of oxygen was added at a time.…”
Section: Colour and Phenolic Evolution Of The Final Extractscontrasting
confidence: 90%
“…Contrary to the findings of Geldenhuys et al (2012), oxygen was also found to play an important role in tannin concentrations (Figure 2 A3). However, Geldenhuys et al (2012) applied progressive micro-oxygenation, whereas in this study a large amount of oxygen was added at a time. A general loss of colour and reduction in phenolic levels was found over time, especially pronounced from 0 M (Table 1) to 3 M, except for the total tannin concentration as determined by the MCP method (Figure 3).…”
Section: Colour and Phenolic Evolution Of The Final Extractscontrasting
confidence: 90%
“…In Table 4.9 are presented the results of the spectrophotometric analyses of wine phenolic compounds. The phenolic content in DMAC index ranged from 231.11 (Vin 9, 2013) to 1104.46 mg/l of catechin equivalents (Vin 8, 2012), with our results being similar to literature (Geldenhuys et al, 2012) for 2013 but twofold increased in 2012.…”
Section: Spectrophotometric Analyses Of Wine Phenolic Compoundssupporting
confidence: 90%
“…() studied the effect of MOX at different SO 2 concentration values and reported a significant decrease in the monomeric anthocyanins and flavan‐3‐ol fractions in wines with a lower SO 2 concentration, together with an increase in the polymeric pigments (Geldenhuys et al. ) and in the concentration of tannins. After a MOX treatment a decrease in the total red pigments occurred, but the proportion of pigments in red form increased (Atanasova et al.…”
Section: Resultsmentioning
confidence: 99%